Association of first-trimester exposure to Kampo medicines containing Prunus persica kernel with preterm birth and major congenital malformations: a Japanese database study - Suzuki, Satoko; Arita, Ryutaro; Obara, Taku; Ishikawa, Tomofumi; Kunitoki, Tadaharu; Sakai, Takamasa; Noda, Aoi; Shinoda, Genki; Ishikuro, Mami; Orui, Masatsugu; Kuriyama, Shinichi; Ohsawa, Minoru; et al. (Frontiers in Pharmacology, 2025)
IntroductionTraditional Japanese (Kampo) medicine containing Prunus persica kernel (KPK) is prescribed for treating menstrual- and pregnancy-related symptoms. However, no safety information is available regarding its use in pregnant women. In this study, we examined the associations of KPK prescriptions during the first trimester of pregnancy with preterm births and major congenital malformations (MCMs) in newborns.MethodsFrom a large-scale Japanese health insurance claims database, we included pregnant women enrolled with the same healthcare insurer from 3 months before pregnancy to the date of delivery, who gave birth between 2010 and 2019, and whose data were linked to their infants. We then selected pregnant women who were prescribed KPK during the first trimester as the exposure group, and those who were prescribed tokishakuyakusan (TSS), commonly used for pregnancy-related symptoms, during the same period as controls. The association between KPK prescriptions and preterm birth or MCM among infants was examined using a multivariate logistic regression analysis.ResultsOf the 75,398 infants, TSS and KPK was prescribed to 2,548 (3.38%) and 283 (0.38%) women during the first trimester, respectively. In the TSS group, 311 of 2,491 infants (12.5%) experienced preterm births, whereas 40 of 283 infants (14.1%) in the KPK group experienced preterm births. The risk of preterm birth in the KPK group was not significantly different from that in the TSS group (adjusted risk ratio, 1.122; 95% confidence interval, 0.827–1.521). In the TSS group, 157 of 2,491 infants (6.3%) had MCMs, whereas 15 of 283 infants (5.3%) in the KPK group had MCMs. There was no significant difference in the incidence of MCM in the first year after birth between infants in the KPK and TSS groups (adjusted odds ratio, 0.820; 95% confidence interval, 0.475–1.415).ConclusionThere was no significant difference in the risk of preterm birth or MCMs between pregnant women prescribed KPK and those prescribed TSS during the first trimester.